Information security: proposal for a VLAN network model - Andrade Arenas, Laberiano Matías (2023)
This article consists of the implementation of a VLAN network in the Hospital Central FAP. The objective is to increase information security, as well as to improve and optimize user data, and this is achieved through the development and use of different protocols, restrictions, and methods that helped to achieve this purpose. Likewise, the article uses the Top-down methodology, which has phases focused on analyzing, developing, and improving the different processes for designing and implementing a VLAN network topology. As a technique, an interview was conducted with the person who, through a series of questions, expressed their opinion on the hospital's problems under study. Data processing was carried out at a qualitative level using Atlas Ti22 software, which allowed the analysis of the perception of 6 people with direct knowledge of the hospital's problems. This information was used to obtain the data for the research work. The result was a high degree of deficiency and disagreement with the system they are currently using. They explained that their data were violated, generating concern among users and all the staff. In addition, the conclusion obtained was that in view of the existing problems, the experts indicated that the proposal related to the implementation of a VLAN Network would meet the desired expectations, providing security to the information, so they consider it a feasible and appropriate option that would be a great alternative for the improvement of the hospital.